Fast growth of undoped and Sn- and Tb-doped ZnO nanowires by Joule heating of Zn. Issue 31 (18th July 2018) - Urbieta, Ana; Sánchez, Víctor; Fernández, Paloma; Piqueras, Javier
Abstract : Joule heating of Zn wires has been used to grow undoped and Sn- or Tb-doped ZnO nanowires in seconds. Abstract : Joule heating of Zn wires by flowing a high electric current density has been used to grow, in times as short as tens of seconds, undoped and Sn- or Tb-doped ZnO nanowires. The contact of tin oxide powder with the starting Zn wire during heating leads to the growth of branched ZnO nanostructures by a catalytic effect of Sn. The growth treatment in the presence of terbium oxide gives rise to a complex ZnO arrangement of nanoparticles attached to nanowires, which show luminescence emission of Tb 3+ transition due to the incorporation of a small amount of Tb into the ZnO nanoparticles during the growth process. The contribution of electromigration, associated with the high electric current density, to the rapid growth of the nanowires, as compared with other thermal-based techniques, is discussed.